1979
DOI: 10.1007/bf00563551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calculation stress on hemodynamics and plasma catecholamines before and after?-blockade with propranolol (inderal�) and mepindolol sulfate (CORINDOLAN�)

Abstract: The effect of calculation stress on hemodynamic parameters and plasma adrenalin and noradrenalin was studied in two groups of 6 male subjects, before and during beta-Blockade. One group received propranolol 15 mg i.v. and the other received mepindolol sulphate 0,5 mg i.v. There was an increase in heart rate, cardiac output and blood pressure during mental stress. A significant increase in plasma adrenalin but not in noradrenalin occurred at the same time. The stress-induced rise in HR but not that in blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
7
1

Year Published

1981
1981
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 11 publications
4
7
1
Order By: Relevance
“…This is evidenced by the fact that plasma norepinephrine levels have been reported to increase,' decrease,' or not change 10 following beta-adrenergic blockade. Nonetheless, a number of studies in animals suggest that, in higher doses, propranolol exerts an additional antihypertensive action either through a decrease in sympathetic nerve activity via central mechanisms, 1113 or adrenergic nerve blockade.…”
Section: Hypertension Vol 3 No 1 January-february 1981mentioning
confidence: 96%
“…This is evidenced by the fact that plasma norepinephrine levels have been reported to increase,' decrease,' or not change 10 following beta-adrenergic blockade. Nonetheless, a number of studies in animals suggest that, in higher doses, propranolol exerts an additional antihypertensive action either through a decrease in sympathetic nerve activity via central mechanisms, 1113 or adrenergic nerve blockade.…”
Section: Hypertension Vol 3 No 1 January-february 1981mentioning
confidence: 96%
“…The progressive fall in PNE from baseline to exercise to recovery that we observed with mental arithmetic parallels these changes, suggesting that a reduction in sympathetic discharge to muscle and an increase in norepinephrine clearance may obscure any increase in sympathetic activity elsewhere. Neither Bonelli et al 41 nor Hjemdahl and Eliasson 25 observed an increase in venous PNE during mental stress. The latter authors found that PNE was increased by tilting but not a color-word conflict test, although this test evoked greater increases in blood pressure and HR.…”
mentioning
confidence: 89%
“…Vasodilation occurs in skeletal muscles, and systemic vascular resistance falls. 41 ' *•** Sympathetic nerve discharge to muscle 33 and norepinephrine release from muscle 46 are reduced. The progressive fall in PNE from baseline to exercise to recovery that we observed with mental arithmetic parallels these changes, suggesting that a reduction in sympathetic discharge to muscle and an increase in norepinephrine clearance may obscure any increase in sympathetic activity elsewhere.…”
mentioning
confidence: 99%
“…It is generally agreed that long-term treatment with ,Badrenoceptor blockers such as propranolol and labetalol causes an increase in the plasma concentration of adrenaline and noradrenaline (Christensen et al, , 1979Carlsen et al, 1980). Therefore it is of interest that Brecht et al (1976), Bonelli et al (1979) and Dominiak & Grobecker (1982) found that the plasma concentrations of catecholamines were reduced after treatment with pindolol, a nonselective 13-adrenoceptor blocker with ISA (Table 1).…”
mentioning
confidence: 99%